2003
DOI: 10.1111/j.1744-6570.2003.tb00152.x
|View full text |Cite
|
Sign up to set email alerts
|

The Core Self‐evaluations Scale: Development of a Measure

Abstract: Despite an emerging body of research on a personality trait termed core self-evaluations, the trait continues to be measured indirectly. The present study reported the results of a series of studies that developed and tested the validity of the Core Self-Evaluations Scale (CSES), a direct and relatively brief measure of the trait. Results indicated that the 12-item CSES was reliable, displayed a unitary factor structure, correlated significantly with job satisfaction, job performance, and life satisfaction, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

49
1,568
4
29

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,559 publications
(1,650 citation statements)
references
References 65 publications
49
1,568
4
29
Order By: Relevance
“…CSE were assessed with the 12-item (e.g., "I am confident that I will get the success I deserve in life") German-language version of the CSE scale by Judge et al (Judge et al, 2003;Stumpp, Muck, Hülsheger, Judge, & Maier, 2010) on a five-point Likert-type scale, 1 (strongly disagree) to 5 (strongly agree). A large number of studies support the validity of the original scale, including its relationships with job satisfaction, career success, and job stress (e.g., Judge, Van Vianen, & De Pater, 2004).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CSE were assessed with the 12-item (e.g., "I am confident that I will get the success I deserve in life") German-language version of the CSE scale by Judge et al (Judge et al, 2003;Stumpp, Muck, Hülsheger, Judge, & Maier, 2010) on a five-point Likert-type scale, 1 (strongly disagree) to 5 (strongly agree). A large number of studies support the validity of the original scale, including its relationships with job satisfaction, career success, and job stress (e.g., Judge, Van Vianen, & De Pater, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…As also cautioned by other researchers (Dobrow & Tosti-Kharas, 2011), one shortcoming of many previous studies investigating the effects of callings on personal and organizational outcomes is that they did not control for relatively stable personal dispositions that might explain the relation between calling and its alleged consequences. For example, empirical studies showed weak to moderate positive correlations between the presence of a calling and CSE (Duffy, Allan, & Bott, in press;Hirschi, 2011), the basic, fundamental appraisal of one's worthiness, effectiveness, and capability as a person (Judge, Erez, Bono, & Thoresen, 2003). Research has also shown that CSE are related to a number of personal, career, and organizational outcomes, including life satisfaction, career self-efficacy, job satisfaction, and vocational identity (Erez & Judge, 2001;Hirschi, 2011;Judge, Van Vianen, & De Pater, 2004).…”
Section: Hypothesis 4: the Indirect Relation Of Calling To Work Engagmentioning
confidence: 99%
“…Beyond demonstrating and validating confirmatory factor analytic fit as well as providing conceptual distinctiveness, when validating any new survey instrument such as used in this study, it is also important to show the nomological network including both antecedents and outcomes of the variable of interest (Judge, Erez, Bono, & Thoresen, 2003). Thus, several other variables were included in the primary study to explore the corresponding semantic network.…”
Section: Additional Study Measuresmentioning
confidence: 99%
“…Accordingly, we align with this more parsimonious yet complete perspective on dispositional employability and operationalize it as a higher-order factor that underlies each of its dimensions (cf. Judge et al, 2003;Forrier, Verbruggen, & De Cuyper, 2015;McArdle et al, 2007).…”
Section: Dispositional Employability and Job Search Intensitymentioning
confidence: 99%
“…As such, it represents a broader and more diversified construct than each of the two narrower dispositions alone (cf. Judge et al, 2003). Second, unlike more general notions of proactivity (e.g., proactive personality), it is a domain specific construct anchored to the work and career context.…”
Section: Introductionmentioning
confidence: 99%